Historical Perspectives of the Environmental and Human Security in the Arctic - Kirchner, Stefan (Palgrave Macmillan, 2019)
The natural environment of the Continental European Arctic, i.e., the northernmost parts of Norway, Finland and Sweden as well as the north-western part of Russia, remains harsh, while simultaneously undergoing major changes. In recent years, this thinly populated land, which has been home to indigenous people for thousands of years, and which is separated by both (relatively) open and hard borders, has significantly gained attractiveness for migrants and visitors alike. Yet, risks to human security persist in the Arctic. By looking at both historical developments and contemporary human rights law, this chapter aims at answering the question of the scope of the obligation of states to protect migrants. It will be shown that there is indeed a positive obligation of states to take the measures which are necessary to protect human lives. This obligation can be fulfilled by providing multi-language information about natural or human-made safety risks.